Analysis of Budget Realization Report of Karo Regency in Fiscal Year 2024 - Azzahra Lidya Almira; Asia Dwi Putri Damanik; Iskandar Muda (CV. Kalimasada Group, 2025)
The Budget Realization Report (LRA) is an important component aimed at evaluating government finances. A published LRA can provide important information. The budget realization report shows the realization of revenues and expenditures. This study aims to determine and evaluate the realization of the Kabupaten Karo government's budget and revenues in 2024 using data from the 2023 and 2024 budget realization reports. In public sector organizations, budgeting can help achieve accountability. The budget realization report shows the difference between the budget and the use of financial resources overseen by the local government. This study uses a quantitative and descriptive methodology using analytical methods such as the analysis of Kabupaten Karo revenue and expenditure. The analysis shows an increase, although not a significant increase, where revenues increased by around 1.3% while expenditures increased by around 5.6%. Kabupaten Karo government has managed its expenditures effectively in this regard.